Reliability of CBCT in the diagnosis of dental asymmetry - Antônio Carlos de Oliveira Ruellas; Leonardo Koerich; Carolina Baratieri; Claudia Trindade Mattos; Matheus Alves Junior; Daniel Brunetto; Lindsey Eidson (Dental Press Editora, 2014)
Objective: The aim of this study was to validate a method used to assess dental asymmetry, in relation to the skeletal midline, by means of CBCT. Methods: Ten patients who had CBCT scans taken were randomly selected for this study. Five different observers repeated 10 landmarks (x, y and z variables for each) and 12 linear measurements within 10 days. Measurements were taken in both arches to evaluate symmetry of first molars, canines and dental midline in relation to the skeletal midline. Intraclass correlation coefficient (ICC) was carried out to assess intra- and interobserver reliability for landmarks and distances. Average mean difference was also assessed to check measurement errors between observers. Results: ICC landmarks was ≥ 0.9 for 27 (90%) and 25 (83%) variables for intra- and interobserver, respectively. ICC for distances was ≥ 0.9 for 7 (58%) and 5 (42%), respectively. All ICC landmarks for distances were >0.75 for both intra- and interobserver. The mean difference between observers was ≤ 0.6 mm for all the distances. Conclusion: The method used to assess dental asymmetry by means of CBCT is valid. Measurements of molars, canines and dental midline symmetry with the skeletal midline are reproducible and reliable when taken by means of CBCT and by different operators.